Charging and discharging model of lithium-ion battery for charge equalization control using particle swarm optimization algorithm - Hoque M.M.; Hannan M.A.; Mohamed A. (American Institute of Physics Inc., 2023)
Charging (batteries); Controllers; DC-DC converters; Electric inverters; Equalizers; Ions; Particle swarm optimization (PSO); Static random access storage; Two term control systems; Voltage control; Algorithmic approach; Battery storage system; Charge and discharge; Charge equalization; Discontinuous current mode; Particle swarm optimization algorithm; PI controller parameters; Proportional-integral control; Lithium-ion batteries